Guilty, But Not Ashamed: "True" Self‐Conceptions Influence Affective Responses to Personal Shortcomings. Issue 3 (14th August 2013) - Vess, Matthew; Schlegel, Rebecca J.; Hicks, Joshua A.; Arndt, Jamie
Abstract The current research examined how true self‐conceptions (who a person believes he or she truly is) influence negative self‐relevant emotions in response to shortcomings. In Study 1 (N = 83), an Internet sample of adults completed a measure of authenticity, reflected on a shortcoming or positive life event, and completed state shame and guilt measures. In Study 2 (N = 49), undergraduates focused on true versus other determined self‐attributes, received negative performance feedback, and completed state shame and guilt measures. In Study 3 (N = 138), undergraduates focused on self‐determined versus other determined self‐aspects, reflected on a shortcoming or neutral event, and completed state shame, guilt, and self‐esteem measures. In Study 4 (N = 75), undergraduates thought about true self‐attributes, an achievement, or an ordinary event; received positive or negative performance feedback; and completed state shame and guilt measures. In Study 1, differences in true self‐expression positively predicted shame‐free guilt (but not guilt‐free shame) following reminders of a shortcoming. Studies 2–4 found that experimental activation of true self‐conceptions increased shame‐free guilt and generally decreased guilt‐free shame in response to negative evaluative experiences. The findings offer novel insights into true self‐conceptions by revealing their impact on negative self‐conscious emotions.